CatacLysMic specificity when targeting myeloid cells?. Issue 6 (19th May 2016) - Blank, Thomas; Prinz, Marco
Abstract : Lysozyme M (LysM) is considered a cell‐specific marker for myeloid cells. An article by Orthgiess et al. in this issue shows, using a Cre‐Lox system in mice, LysM expression in brain neurons, with low expression in myeloid microglia. This raises concerns regarding microglia and peripheral myeloid targeting using LysM‐Cre mice. Abstract : The antibacterial enzyme lysozyme M (LysM) encoded by the Lyz2 gene is broadly expressed in myeloblasts, macrophages, and neutrophils, and thus has been used for a long time as a cell‐specific marker for myeloid cells in mice. In order to delete loxP‐site flanked genes in myeloid cells, a Cre‐recombinase (Cre) expressing mouse line was created by inserting Cre‐coding sequence into the translational start site of the LysM gene. In this issue of the European Journal of Immunology [2016. 46: 1529–1532], Orthgiess et al. verify, with the help of tdTomato and YFP reporter mouse lines, LysM ‐driven recombination. Unexpectedly, the authors also describe major expression of the tdTomato reporter protein in brain neurons of the central nervous system (CNS), with only a very small percentage of gene recombination in myeloid cells of the brain, called microglia. These findings cause justified concerns regarding the efficient and specific targeting of microglia and peripheral myeloid cells using LysM‐Cre mice and should stimulate thoughts on conclusions drawn from past experiments on the diseased CNS employing this Cre/loxP‐deleter line.